L’ordinateur et le facteur humain - Ricard, Hubert (Assurances)

(untitled) (HEC Montréal, 1981)
Maximum results can only be obtained when the user works closely with the computer. In his article, Mr. Ricard stresses the importance of the human factor, as individuals do, in practice, demand that electronic processing equipment function at optimum capacity.